# How do you differentiate #f(x) = 3x(e^((x-9)^2))^3# using the chain rule?

Step 1. Simplify the exponent

Step 2. Using the Product Rule directly uses the chain rule.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you differentiate #f(x)= 7xsinx# using the product rule?
- How do you find the derivative of #y = (x^2 + sqrtx + 1 ) / x^(3/2)#?
- How do you find the derivative of # f(x) = 1/sqrt(x) #?
- How do you differentiate #s=(t^2+1)/(1-t^2)#?
- How do you find #dy/dx# by implicit differentiation given #e^x=lny#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7